(untitled) (International Journal of Biology and Chemistry, 2018)
The results of investigation adsorption mechanism of diisopropyldithiophosphate collector on the surface of the sulfide copper ore and flotation has been discussed. The investigation of composition and structure of sulphide copper ore has been carried out by using FT-IR-spectroscopy, Х-ray diffraction spectroscopy and ICP-MS method. The results showed that sorption capacity of ore at pH 10.5-11.5 is a maximum. The role of the oxidation-reduction processes in fixing of diisopropyldithiophosphate ion on the surface of ore was established. It was shown that data of extraction of copper to concentrate and adsorption value of diisopropyldithiophosphate ion are correlating. The IR-Fourier spectroscopic analysis showed that collector is coordinated with the ions of the metal of the crystal lattice of copper-containing minerals through the sulfur atoms of the dithiophosphate group.